1980
DOI: 10.1083/jcb.84.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of type III collagen by fibroblasts from the embryonic chick cornea

Abstract: Synthesis of collagen types I, II, III, and IV in cells from the embryonic chick cornea was studied using specific antibodies and immunofluorescence . Synthesis of radioactively labeled collagen types I and III was followed by fluorographic detection of cyanogen bromide peptides on polyacrylamide slab gels and by carboxymethylcellulose chromatography followed by disc gel electrophoresis .Type III collagen had been detected previously by indirect immunofluorescence in the corneal epithelial cells at Hamburger-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Whereas col I was expressed by both cell lineages, there was no immunoexpression of col III in none of the studied cells. It has been suggested that treatment of cells with proteolytic enzymes, for instance trypsin digestion, leads to a greater degradation of col III relative to col I (Conrad et al. 1980, Van Amerongen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas col I was expressed by both cell lineages, there was no immunoexpression of col III in none of the studied cells. It has been suggested that treatment of cells with proteolytic enzymes, for instance trypsin digestion, leads to a greater degradation of col III relative to col I (Conrad et al. 1980, Van Amerongen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Such localization indicates that the long form of Type XII collagen mediates periodic interactions between collagen fibrils and other extracellular matrix components to stabilize them. In fact, Types I, II, III, IV, V VI, IX, XIV, and XVII collagen molecules were detected immunohistochemically in avian cornea (Conrad et al 1980;Linsenmayer et al 1984Linsenmayer et al ,1986Birk et al 1986;Fitch et al 1988Fitch et al ,1990Sugrue 1991;Chen et al 1993;Watanabe et al 1994;Gordon et al 1996Gordon et al ,1997Doane et al 1998). Among them, Types IX and XIV are associated with collagen fibrils, Type IX collagen forms a complex with Type II collagen in the primary corneal stroma (Fitch et al 1988Cai et al 1994), and structurally related Types XII and XIV collagen molecules also form complexes with Type I collagen (Koch et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Upon migration into the region of the presumptive cornea, neural crest cells down-regulate HNK-1 [59], transform from mesenchymal to fibroblastic morphology [33], and initiate the expression of molecular markers such as collagens, keratan sulfate, and chondroitin sulfate [60][61][62][63]. During subsequent development, the newly formed keratocytes synthesize the extracellular matrix and maintain the transparency of the corneal stroma.…”
Section: Discussionmentioning
confidence: 99%